Belonging and Social Integration as Factors of Well-Being in Latin America and Latin Europe Organizations - da Costa, Silvia; Martínez-Moreno, Edurne; Díaz, Virginia; Hermosilla, Daniel; Amutio, Alberto; Padoan, Sonia; Méndez, Doris; Etchebehere, Gabriela; Torres, Alejandro; Telletxea, Saioa; García-Mazzieri, Silvia (Frontiers in Psychology, 2020)
Background: Studies and meta-analyses show a series of factors at the individual, meso and micro-social level that are associated with individual well-being, as well as a positive socio-emotional climate or group hedonic well-being. Aim: This article simultaneously studies and examines these factors of well-being. Method: Well-Being is measured as a dependent variable at the individual and collective level, as well as the predictors, in three correlational studies and a longitudinal one. Education and social intervention workers (N = 1300, K = 80) from Chile, Spain and Uruguay participate; a subsample (k = 1, n = 37) from the south central Chile; workers from organizations in Latin America and Southern Europe, military cadets from Argentina (N < 1000); and teams (K = 14) from Spanish companies. Results: Individual factors, and indicators of commitment and job satisfaction are associated with well-being and socio-emotional climate. Micro-level factors such as participation and communication, task orientation, as well as leadership styles that contribute to participation and integration in groups and teams, are associated with a better socio-emotional climate. Transformational leadership plays a mediating role between factors and socio-emotional climate at the team level. While work control and social support from peers and supervisors are positively associated with well-being, excessive psychological demands at work - or stress - do so negatively. Similarly, the challenge and complexity of the role is positively associated with group well-being. Meso-level factors such as an inclusive and participatory culture are directly and indirectly associated with well-being through psychosocial factors favorable to it. Role challenge and complexity, positive leadership, as well as an integrated and resourceful organizational culture are associated with a better emotional climate. Controlling the gender and transformational style of the immediate leader, organizational leadership moderates the relationship between task orientation and socio-emotional climate in the military environment. Conclusions: Factors favorable to well-being at the meso level, through micro-social processes, which reinforce social belonging, influence on psychological well-being, with stress and emotional climate playing an important role.